Scleral Contact Lenses in an Academic Oculoplastics Clinic: Epidemiology and Emerging Considerations. Issue 3 (May 2018) - Chahal, Harinder S.; Estrada, Marcela; Sindt, Christine W.; Boehme, Jacob A.; Greiner, Mark A.; Nerad, Jeffrey A.; Carter, Keith D.; Allen, Richard C.; Shriver, Erin M.
Abstract : Purpose: To describe the role and efficacy of scleral contact lenses (SCLs) in the treatment of progressive keratopathy in patients who have undergone periocular surgical procedures, to investigate the financial impact of these surgical interventions, and to demonstrate the role of oculoplastic surgery in improving scleral contact lens fit. Methods: A retrospective medical record review was performed to identify patients who both received SCLs and were examined by the oculoplastics service at the University of Iowa between January 1990 and December 2015. Inclusion criteria also required a minimum of 12 months of patient follow up after being fit with a SCL. The indication for SCL use, as well as clinical outcomes and cumulative relative value units (RVUs) of prior oculoplastic treatments and SCL therapy were recorded for each patient. Results: Six hundred and fifty-nine patients were fitted with SCLs at the authors' institution during the 25-year study period, 43 of whom were examined by the oculoplastics service for reasons related to their SCL. Patients who were fitted for SCLs before (27 patients) or after (16 patients) evaluation in the oculoplastics clinic presented with a variety of corneal and periocular pathology. Corneal indications for SCLs in patients seen secondarily in the oculoplastics clinic included decreased corneal sensation (from CN V palsy or neurotrophic keratopathy), decreased corneal healing from limbal stem cell deficiency, exposure keratopathy, and keratoconjunctivitis sicca secondary to Sjogren's syndrome or orbital radiation. Indications for oculoplastic clinic evaluation in current scleral lens patients included lagophthalmos, trichiasis, epiphora, cicatricial changes in the eyelids or fornices, and eyelid or eyebrow malposition affecting SCL centration. In all 27 patients, surgical intervention resulted in improved SCL centration. Sixteen patients (5 with CN VII palsy, 4 with CN V and CN VII palsy, 4 with neurotrophic keratitis, and 3 with cicatricial entropion) had progressive corneal decompensation despite primary oculoplastics procedures to protect the cornea and ultimately benefitted from SCL treatment secondarily. Fourteen of these 16 patients demonstrated an improved visual acuity of 1 line or more using SCLs. Procedures performed before referral for SCLs included tarsorrhaphies, gold weights, ectropion repair with lateral tarsal strip, retraction repair with spacer grafts, full-thickness skin grafts, cheek lifts, and punctal occlusion. The total RVUs of these procedures performed per patient were tabulated. The RVU range was 10.47–33.96 with an average of 19.5 RVUs (standard deviation = 9.4 RVUs) per patient. Conclusions: Scleral contact lenses may offer a useful alternative to stabilize the ocular surface, improve vision, and minimize the financial impact and morbidity of multiple periocular procedures in select patients with progressive keratopathy of varying etiologies. The therapeutic indications and utilization of SCLs are likely to increase in oculoplastic practices with optometric support, particularly in academic settings. Surgical correction of eyelid and eyebrow malposition, as well as epiphora, may also be useful adjunctive procedures to optimize SCL fit. Abstract : Scleral contact lenses have an emerging role in oculoplastic care. Oculoplastic surgeons should be familiar with these lenses and their increasing clinical relevance.